INQUIRY LEARNING MODEL WITH APPROACH TEACHING AT THE RIGHT LEVEL (TARL) TO COMPLETE STUDENT LEARNING OUTCOMES ON SALT HYDROLYSIS MATERIALS IN CLASS XI IPA 3 SMAN 1 MANYAR GRESIK - Fadlilah, Anis; Lutfi, Achmad; Hermynyawati, Emy (JCER (Journal of Chemistry Education Research), 2024)
The purpose of this study is to evaluate the completeness of learning outcomes in the application of the inquiry learning model with the Teaching at the Right Level approach to salt hydrolysis material. The subjects of this study were 35 students in class XI IPA 3 at SMAN 1 Manyar Gresik. Two cycles of classroom action research were conducted. The observation method and the test method are the methods used to acquire data. Based on the results of the analysis and discussion, it can be concluded that the application of the inquiry learning model with the Teaching at the Right Level (TaRL) approach in class XI IPA 3 SMAN 1 Manyar Gresik can complete student learning outcomes. The success of this application can be seen from the percentage of completeness in cycle I of 77.14% then increased in cycle II of 82.86%.